Pengembangan LKPD Model Problem Based Learning Berorientasi Aktivitas Berpikir Kritis Pada Materi Getaran, Gelombang, dan Bunyi di Kelas VIII SMPN 3 Padang - Amelia Putri; Amali Putra (Universe, 2021)
Activities and critical thinking skills of students in science learning at SMPN 3 Padang still unable to make students solve the problems that given by the teacher, it is caused by several factors, such as the use of media and learning models that are not in accordance with the topic that the teacher gave. The solution to these problems is to integrate learning models and instructional media that are in accordance with the subject matter. One of them is developing student worksheet model of problem based learning oriented on critical thinking activities. The research model that we used is Research and Development (R&D) using a 4-D model consisting of four stages, they are the define, design, develop, and dessiminate step, but the dessiminate stage is not carried out due to time and cost limitations. Based on data analysis, the results of the student worksheet validity value of 91.27 are in the very valid category. So it can be concluded that the student worksheet model of problem based learning oriented on critical thinking activities is very valid to be used for grade VIII students of SMPN 3 Padang.